Mapping of second growth forest using forest canopy density model technique - a case study / Khali Aziz Hamzah ... [et al.] - Hamzah, Khali Aziz; Ibrahim, Shamsudin; Muhammad Yusof, Shafiah @ Yusmah; Shah Idris, Abdul Azahan; Hashimi, Rodziah; Chin, Yue Mun; Mohd Ariff, Zainudin (2002)
Forest Management practices can be improved through the use of current technologies including remote sensing, Geographic Information System (GIS) and Global Positioning System (GPS). One approach where remote sensing data can be used effectively to map forest conditions is by using Forest Canopy Density model (FCD Mapper). FCD Mapper is a semi-expert system developed by the International Tropical Timber Organisation (ITTO). The model utilises forest canopy density as an essential parameter for characterisation of the forest conditions. Hence it is possible to monitor forest conditions over time using multi-temporal satellite images base on this model. Landsat TM data is the main input to the model and the analysis focuses on four indices namely the Advanced Vegetation Index (A VI), Bare Soil index (B1), Shadow Index or Scaled Shadow Index (SI, SSI) and Thermal Index (TI). These four indices have direct relationship with the forest conditions. The model produces forest canopy density map, which may indicates the intensity of rehabilitation treatment needed in the particular area. This is very useful in planning and implementation of any forest rehabilitation programmes. This paper highlights the usefulness of this technique in mapping logged-over forest for resource assessment purposes.